Pengaruh Model Pembelajaran Problem Based Learning (PBL) terhadap Hasil Belajar Matematika Siswa - Sabrun, Sabrun (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
The problem in this research is the low mathematics learning outcomes of students. This is because the teaching methods used are still monotonous. The aim of this research is to determine the effect of the problem based learning cooperative learning model on the mathematics learning outcomes of class XI students at SMA Negeri 2 Labuapi. The type of research used in this research is a quasi experiment with a pre-test post-test control group design. The population in this study were class XI students of SMA Negeri 2 Labuapi. The sample for this research was class XIA as the experimental class and XIB as the control class. The sampling technique uses saturated sampling. The instrument of this research is a test sheet. Based on the results of data analysis on student mathematics learning outcomes, the average score in the experimental class was 81.33 with the highest score being 100 and the lowest score being 65, while the average score in the control class was 60.17 with the highest score being 80 and the lowest score being 40. Based on the results of the t test, tcount is 8.298 and ttable is 2.002, because tcount ≥ ttable then Ha is accepted and H0 is rejected. So, it can be concluded that there is an influence of the problem based learning type cooperative learning model on the mathematics learning outcomes of class XI students at SMA Negeri 2 Labuapi.